2021
DOI: 10.3329/ajmbr.v7i1.53305
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the spread of COVID-19 pandemic in Bangladesh using ARIMA model

Abstract: COVID-19 is one of the most serious global public health threats creating an alarming situation. Therefore, there is an urgent need for investigating and predicting COVID-19 incidence to control its spread more effectively. This study aim to forecast the expected number of daily total confirmed cases, total confirmed new cases, total deaths and total new deaths of COVID-19 in Bangladesh for next 3 weeks. The number of daily total confirmed cases, total confirmed new cases, total deaths and total new deaths of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Kundu et al. 16 predicted the expected number of confirmed cases, confirmed new cases, total deaths, and total new deaths in Bangladesh. Nyoni et al.…”
Section: Introductionmentioning
confidence: 99%
“…Kundu et al. 16 predicted the expected number of confirmed cases, confirmed new cases, total deaths, and total new deaths in Bangladesh. Nyoni et al.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, Kundu et al (2021) forecasted the expected number of total confirmed cases, total confirmed new cases, total deaths, and total new deaths in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%